Removal of Pb (II), As (III), and Cr (VI) by nitrogen‐starved Papiliotrema laurentii strain RY1. (20th August 2019) - Sarkar, Soumyadev; Mukherjee, Avishek; Parvin, Rubia; Das, Subhadeep; Roy, Uttariya; Ghosh, Somdeep; Chaudhuri, Punarbasu; Roychowdhury, Tarit; Mukherjee, Joydeep; Bhattacharya, Semantee; Gachhui, Ratan
Abstract: Heavy metals such as lead, chromium, and metalloid like arsenic dominate the pinnacle in posing a threat to life. Being environment‐friendly, elucidating the mechanism by which microorganisms detoxify such elements has always been an active field of research hitherto. In the present study, we have investigated the capability of nitrogen‐deprived Papiliotrema laurentii strain RY1 toward enhanced tolerance and neutralizing toxic elements. There were biosorption and bioprecipitation of lead and chromium at the cell surfaces. Bioprecipitation mechanisms included the formation of lead phosphates and pyromorphites from lead, grimaldite from chromium. Transcripts such as metallothionein, aquaporins, and arsenical pump‐driving ATPase have been surmised to be involved in the detoxification of elements. Furthermore, activation of antioxidant defense mechanisms for the cells for each of the elements should contribute towards yeast's propagation. The efficiency of removal of elements for live cells and immobilized cells were high for lead and chromium. To the best of our knowledge, this is the first report of such high tolerance of lead, arsenic, and chromium for any yeast. The yeast showed such varied response under dual stress due to nitrogen starvation and in the presence of respective elements. The yeast possesses promising potentials in nitrogen deprived and enriched environments to aid in bioremediation sectors.